2021
DOI: 10.3389/fonc.2021.647110
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clinical Trials on Therapies for Prostate Cancer in Mainland China and Globally from 2010 to 2020

Abstract: The overall aging of the world population has contributed to the continuous upward trend in the incidence of prostate cancer (PC). Trials on PC therapy have been extensively performed, but no study has analyzed the overall trends and characteristics of these trials, especially for those carried out in China. This study aimed to provide insights on the future direction of drug development in PC, thus supplying essential supportive data for stakeholders, including researchers, patients, investors, clinicians, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…According to the data from GLOBOCAN, 1,276,106 new cases of PC were documented worldwide in 2018, with a higher incidence in the Western countries [ 1 ]. In China, 120,000 new cases were reported in 2016, and PC is ranked the ninth malignant tumor in men [ 3 , 4 ]. Even if the 5-year survival rate of PC is more than 99%, patients with metastatic PC only have about 31% of the 5-year survival rate [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the data from GLOBOCAN, 1,276,106 new cases of PC were documented worldwide in 2018, with a higher incidence in the Western countries [ 1 ]. In China, 120,000 new cases were reported in 2016, and PC is ranked the ninth malignant tumor in men [ 3 , 4 ]. Even if the 5-year survival rate of PC is more than 99%, patients with metastatic PC only have about 31% of the 5-year survival rate [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In line with this finding, in a recent review on clinical trials for drug development in rare diseases, the authors found out that a small number of rare diseases (mostly cancer-related) contributed to the majority of trials and investigated drugs (39), hence, chemotherapeutic drugs were the most abundant in the top 20 tested drugs. In contrast, a study by Chen et al on therapies for prostate cancer in China found that clinical trials were focused mainly on hormonal therapy (41.5%), chemotherapy (31.3%) and immunotherapy (20.7%) (40). This may be explained by the different types of treatment options due to different pathogenesis for these distinct cancers, which is reflected in the different profile of investigated therapies within clinical trials.…”
Section: Limitations Of the Studymentioning
confidence: 97%
“…Prostate diseases are prevalent worldwide and are among the most common diseases of the male genitourinary system. PCa is the second most common cancer in men globally, with a mortality rate second only to lung cancer [ 1 , 2 ]. Currently, there are multiple theories and hypotheses regarding the pathogenesis of PCa, but the exact causes are still unclear.…”
Section: Introductionmentioning
confidence: 99%